Pengembangan E-komik Media Pembelajaran Menulis Teks Negosiasi - Pratami, Fisnia; Devita Sari, Nindy; Hidayani, Nuri; Supriyadi, Randi (Universitas PGRI Palembang, 2024)
The purpose of this research is to explain the development process and appeal of E-comics as a learning tool in negotiating text materials for tenth-grade classes. The research method employed is research and development, following the ADDIE model consisting of 5 steps: 1) analysis, 2) design, 3) development, 4) implementation, and 5) evaluation. The focus of the study is on the third stage, in accordance with the established objectives. The research instrument uses a Likert scale questionnaire, with analysis conducted using predetermined percentages. The research findings indicate that E-comics as a teaching tool for negotiating text in tenth-grade classes are considered feasible and usable, supported by validation from three experts in the fields of content and instructional media. Trials involving three Indonesian language teachers at SMAN 1 Buay Madang Timur also show the suitability of E-comics. Positive responses from students regarding the appeal of E-comics are also evident, with several indicators showing a significant level of appeal. Therefore, it can be concluded that E-comics are considered attractive. The hope of this developmental research is that it can be implemented in the learning process by researchers in the future.